TINJAUAN IKONOGRAFI DAN IKONOLOGI POSTER IKLAN RED BULL œPOWER ON FOR STRENGTH - Muryasari, Desiana; Rohiman, Rohiman; Mahendra, Iqbal (Gorga : Jurnal Seni Rupa, 2024)
Red Bull is an energy drink brand owned by Red Bull GmbH from Austria. With a share of Red Bull is an energy drink brand owned by Austrian company Red Bull. With a market share of 38%, Red Bull became the world's most popular energy drink brand in 2019. Rather than relying on traditional marketing methods, Red Bull gained attention and built a œbrand myth through several extreme sports series. Red Bull has repeatedly used nonverbal forms of signs and signals (icons) when designing advertising posters for its products. What is interesting to study is that the symbols used in Red Bull product advertisements have an important and lasting role. The purpose of this study is to identify the signs and markings on Red Bull's œPower on for Strength advertising posters. The qualitative research method uses a historical approach. This research review is historical and based on Erwin Panofsky's theory of iconography and iconology. Translated with DeepL.com (free version). The iconography review emphasizes the themes and concepts in the Product advertising posters. The first conclusion regarding the visual design of the Red Bull œPower On For strength advertising poster has factual and representational meanings. The main object is factual in the object of can packaging and the Power icon which is explicitly an expression of Red Bull can packaging is strength. The second conclusion is the theme of the advertisement about the representation of recognizable objects. The representation of familiar objects is often used to express the objective relationship between the sign of an object in the icon and the real object. The third conclusion is the meaning of the Red Bull advertising poster œPower On For Strength Red Bull product identification process through the shape and icon of power on the object of can packaging. The can packaging symbolizes the product name Red Bull, and the Power icon as a sign of power. Using the power icon means that drinking Red Bull increases energy in the body, in other words making you feel like you just woke up.Keywords: Advertising, Poster, Iconography, Iconology, RedBullAbstrakRed Bull merupakan sebuah merek minuman energi milik Red Bull GmbH asal Austria. Dengan pangsa Red Bull adalah merek minuman energi yang dimiliki oleh perusahaan Austria Red Bull. Dengan pangsa pasar sebesar 38%, Red Bull menjadi merek minuman energi terpopuler di dunia pada tahun 2019. Daripada mengandalkan metode pemasaran tradisional, Red Bull mendapatkan perhatian dan membangun "mitos merek" melalui beberapa seri olahraga ekstrim. Red Bull telah berulang kali menggunakan bentuk  tanda dan tanda (ikon) nonverbal ketika merancang poster iklan untuk produknya. Yang menarik untuk dikaji adalah simbol yang digunakan dalam  iklan produk Red Bull mempunyai peranan penting dan abadi. Tujuan dari penelitian ini adalah untuk mengidentifikasi tanda dan penandaan pada poster iklan œPower on for Strength Red Bull. Metode penelitian kualitatif menggunakan pendekatan sejarah. Tinjauan  penelitian ini bersifat historis dan didasarkan pada teori ikonografi dan ikonografi Erwin Panofsky. Tinjauan ikonografi menekankan kepada tema dan konsep pada poster iklan Produk. Kesimpulan pertama mengenai desain visual poster iklan Red Bull œPower On For trength'' memiliki makna faktual dan representasionalnya. Objek utama bersifat faktual ialah pada objek kemasan kaleng dan ikon Power yang secara eksplisit bersifat ekspresi dari kemasan kaleng Red Bull ialah kekuatan. Kesimpulan kedua tema iklan tentang representasi objek yang mudah dikenali. representasi objek yang familiar sering digunakan untuk mengungkapkan hubungan objektif antara tanda suatu objek dalam ikon dan objek nyata. Kesimpulan ketiga adalah makna poster iklan Red Bull œPower On For Strangth Red Bull proses identifikasi produk melalui bentuk dan ikon power pada objek kemasan kaleng. Kemasan kaleng melambangkan nama produk Red Bull, dan ikon Power sebagai tanda bentuk kekuasaan. Menggunakan ikon power berarti meminum Red Bull meningkatkan energi dalam tubuh, dengan kata lain membuat Anda merasa seperti baru bangun tidur.Kata Kunci: Iklan, Poster, Ikonografi, Ikonologi, RedBullAuthors:Desiana Muryasari : Institut Informatika dan Bisnis DarmajayaRohiman : Institut Informatika dan Bisnis DarmajayaIqbal Mahendra : Institut Informatika dan Bisnis DarmajayaReferencesAppel, G., Grewal, L., Hadi, R., & Stephen, A. T. (2020). The future of social media in marketing. Journal of the Academy of Marketing Science, 48(1), 79“95. https://doi.org/10.1007/s11747-019-00695-1Burhan, M. A. (2008). Perkembangan Seni Lukis Mooi Indie sampai Persagi di Batavia, 1900-1942. Jakarta. Galeri Nasional Indonesia.Burhan, M. A. (2015). Lukisan Ivan Sagita œMakasih Kollwitz (2005) dalam Sejarah Seni Lukis Modern Indonesia: Tinjauan Ikonografi dan Ikonologi. Panggung, 25(1), Article 1. https://doi.org/10.26742/panggung.v25i1.10Firat, D. (2019). YouTube advertising value and its effects on purchase intention. Journal of Global Business Insights, 4(2), 141“155. https://doi.org/10.5038/2640-6489.4.2.1097Justin, M. R., Rohiman, R., Moussadecq, A., Darmawande, A., & Ramadhan, A. A. (2023). Iklan Layanan Masyarakat Sebagai Media Kampanye Sosial Bahaya Adiksi Game Online. Gorga¯: Jurnal Seni Rupa, 12(1), 48. https://doi.org/10.24114/gr.v12i1.42857Official Website., R. B. E. D. (2024). Red Bull Energy Drink”Official Website. https://www.redbull.com/id-id/energydrink/company-profilePanofsky, E. (1955). Meaning in the Visual Arts. Doubleday & Company, Inc.Ramadhan, A. Z. (2020). Analisis Semiotika Iklan Cetak La Lights œJangan Mau Diadu Versi Ayam. Gorga: Jurnal Seni Rupa, 9(2), Article 2. https://doi.org/10.24114/gr.v9i2.19551Rohiman, R., Mousadecq, A., Darmawan, A., & Ramadhan, A. A. (2022). Kajian Tanda Pada Poster Iklan Produk IKEA. Prosiding Seminar Nasional Darmajaya, 1(0), Article 0.Rohiman, R., Moussadecq, A., & Widakdo, D. T. (2022). Ornamen Kapal Lampung Typeface. Gorga¯: Jurnal Seni Rupa, 11(2), 439. https://doi.org/10.24114/gr.v11i2.38959Schouten, A. P., Janssen, L., & Verspaget, M. (2020). Celebrity vs. Influencer endorsements in advertising: The role of identification, credibility, and Product-Endorser fit. International Journal of Advertising, 39(2), 258“281. https://doi.org/10.1080/02650487.2019.1634898Utoyo, A. W. (2020). Analisis Komunikasi Visual Pada Poster Sebagai Media Komunikasi Mendorong Jarak Sosial Di Jakarta Saat Epidemi Covid 19. LUGAS Jurnal Komunikasi, 4(1), 35“42. https://doi.org/10.31334/lugas.v4i1.939